Incidence and risk factors of VTE in patients with cervical cancer using the Korean national health insurance data - Yuk, Jin-Sung (Sci Rep, 2021)
This study investigated incidence and risk factors for venous thromboembolism (VTE) in patients with cervical cancer. We selected 49,514 patients newly diagnosed with cervical cancer from the Korean Health Insurance Review and Assessment Service databases. During the total follow-up period and first 6 months after initiation of primary treatments, incidence of VTE, and association of risk factors with VTE occurrence were evaluated according to primary treatments or no treatment, surgery, radiotherapy, and chemotherapy. VTE occurred in 1.15% of patients with cervical cancer. Regardless of the period after initiation of primary treatments, and of VTE, the incidence of thromboembolism was highest in chemotherapy. During the first 12 months, monthly incidence of VTE was highest in chemotherapy and decreased with time in all primary treatments. Compared with no treatment, VTE risk significantly increased for all primary treatments (surgery: HR 1.492; 95% CI 1.186–1.877) (radiotherapy: HR 2.275; 95% CI 1.813–2.855) (chemotherapy: HR 4.378; 95% CI 3.095–6.193) and for chemotherapy during the first 6 months (HR 3.394; 95% CI 2.062–5.588). In this cohort study, incidence and risk of VTE in patients with cervical cancer were the highest when chemotherapy was the primary cancer treatment, and incidence of VTE decreased with time.